DEVELOPMENT OF A WEB-BASED TOULOUR REGIONAL LANGUAGE CORPUS USING THE SYSTEM DEVELOPMENT LIFE CYCLE METHOD - Lipan, Kezia; Rantung, Vivi P.; Rorimpandey, Gladly C. (Informatika, Universitas Jenderal Soedirman, 2024)
Language is a tool for communicating with interlocutors Indonesia is a country that uses Indonesian as an official language, but Indonesia is a multilingual country with 719 regional languages ​​in Indonesia, some of which are classified as endangered. One of the Indonesian regional languages ​​is the Toulour regional language which is one of the regional languages ​​of the Minahasa tribe where the use of the Toulour language is currently decreasing due to the increasing use of the Manado Malay language, making the Toulour language increasingly shifting and threatened with extinction. This research aims to build language resources, namely a corpus, for linguistic researchers to create a dictionary that can later be accessed digitally. This research uses the System Development Life Cycle method, a system development stage. The result of this research is a corpus analysis website that shows 6 corpus analysis techniques, namely word frequency, concordance, tokens, collocations, n-grams, and word lists. There is a download-all token feature for users which can later be utilized by the researcher. Users can also carry out their analysis by entering language text and concordances, collocations, and n-grams, users can also search for them with one keyword.